Implementation of PES 2019 Based Learning Media in the Basic Football Skills Course - Prabowo, Andika; Rizky, Oddie Barnanda; Panca, Yusran; Ilahi, Bogy Restu; Raibowo, Septian; Permadi, Andes (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective: The newness of learning media is considered very important to support the learning process, the use of visual technology-based media and comprehensive applications and video games are considered to be able to answer problems that occur in the learning process, this study aims to facilitate and measure the effectiveness of learning media in Physical Education Study Program students with the renewal of learning media based on the PES application 2019 in the basic football skills course, Materials And Method: used in this study is experimental with a two-group design with a quantitative approach, the population and sample amounting to 86 people consisting of all students of the Physical Education Study Program at the University of Bengkulu semester 3. Result: this study shows an increase in learning outcomes, the results of the differential test obtained a th value of 1.988 > Sig 0.05, the contribution given by PES 2019-based learning media is 91% to learning outcomes, which proves the influence of the implementation of learning media Conclusions: The use of the PES 2019 application has a significant influence on the results of basic football learning in the Physical Education study program at the University of Bengkulu